Design of corporate foundations construction and operation of logistics systems in the economic system of the State - Kunyazov, E.K.; Grebnev, L.S. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with modern practical and methodological aspects of the construction of logistics systems, in relation to the economic system of the Republic of Kazakhstan. Particular attention is focused on a macro and sub micrologistical systems infrastructure aspects of their development, taking into account the factors of the global economy. Given the focus of logistics systems in the macroeconomic effect is picked their prospective role in the development of Kazakhstan's economy, affecting the innovative aspects of the development of industry and business processes. In the long term logistics system can be widely spread and development not only in terms of material flow, but also from the perspective of an information component, driving dynamics HR-resources that will allow optimal integration of the economy of Kazakhstan in global and cross-border production and economic systems. As a consequence, it can be designed new economic theory of building and designing the logistics of foreign alliances, cooperation between the customs authorities, improving the principles and methodology of the competition in the international markets for goods and services. The theoretical studies are applied and can be widely distributed in practice within the framework of improving the functioning of the Customs Union «Kazakhstan - Russia – Belarus». The main research methods were used - a systematic approach, analysis and synthesis, observation, theoretical analysis.